Blow-up criteria for coupled nonlinear Schödinger equations. Issue 3 (11th February 2023) - Bai, Qianqian; Li, Xiaoguang; Zhang, Jian
Abstract : This paper deals with the blw-up problem of a system of two coupled nonlinear focusing Schrödinger equations. By using localized virial estimates, we establish a blow-up criteria for non-radial solutions without the hypothesis of finite variance.